The Relationship of Innovation Capabilities Towards Employees’ Perormance: Mediating Effect of Tecnoloical Diersity in UAE Manufacturing Companies - Md Fauzi Ahmad; Hamdan Sohail Obaid Alhefeiti; Mohd Nasrun Mohd Nawi; Arman Shah Abdullah (International Journal of Supply Chain Management, 2019)
Towards Employees’ Performance: Mediating Effect of Technological Diversity in UAE Manufacturing Companies